Characteristic, Behaviour, Lung Function of Workers and PM2,5 Concentration in Cecek Home Industry Sidoarjo Regency - Zuhrida Aulia; R. Azizah (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: PM2,5   as  one  of the  air pollutions  parameters can  be  derived from burning  wood. Negative impact  from PM2,5  exposure on health are impaired  lung function.  This study  was conducted to analyze  characteristics, behaviors, lung function  of workers  and PM2,5  concentration in cecek home industry Katerungan  Village, Krian District of Sidoarjo Regency. This research used cross sectional design with total population, 10 workers.  Indoor PM2,5 concentration in production area and  warehouse space were  measured using  EPAM 5000  and  workers  lung function  was  measured using spirometry test. Individual characteristics and behaviors of workers  were analysed using descriptive quantitatively to lung  function.  Individual characteristics variable consists of age,  job tenure,  medical history and  BMI. Behavioral variables focus on smoking habit. The result of this research showed that PM 2.5 concentration in production area and warehouse space still under  the environmental quality standards (< 10 mg/m3). 40% workers  in production area and 80% workers  in warehouse space got impaired  lung function.  We can conclude that impaired  lung function  of workers in cecek home industry Katerungan  Village, Krian District of Sidoarjo Regency is not caused of PM2,5 exposure, but job tenure,  medical history, BMI, smoking habit for more than 5 years and more than 1 pack  per day. Impaired lung function more  likely happen to worker with job tenure  more  than 5 years,  having  historical respiration  disease, having  wasted nutritional status  and have been smoked more than 5 years and more than 1 pack  per day. The suggestion is that workers with impaired  lung function  should have  advanced diagnosis and  therapy.  For the owner  of a home industry,  should require his workers wearing  masks at work place.Keywords: PM2,5, lung function,  cecek home industry